Evaluate the effectiveness of education through video on removable media - Hasan, Tarik; Islam, Majharul; Hayat, Gazi Showket (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2007.